A rapid procedure for the isolation of the Lys-49 myotoxin II from Bothrops moojeni (caissaca) venom: Biochemical characterization, crystallization, myotoxic and edematogenic activity - Soares, A. M.; Rodrigues, V. M.; Homsi-Brandeburgo, M. I.; Toyama, M. H.; Lombardi, F. R.; Arni, R. K.; Giglio, JR (Elsevier B.V., 1998)
A, M. Soares, V, M, Rodrigues, M. I. Homsi-Brandeburgo, M. H. Toyama, F, R, Lombardi, K. Arni and J. R, Giglio. A rapid procedure for the isolation of the Lys-49 myotoxin II from Bothrops moojeni (caissaca) venom: Biochemical characterization, crystallization, myotoxic and edematogenic activity. Toxicon 36, 503-514, 1998.-Bothrops moojeni snake venom was fractionated on a CM-Sepharose column which was previously equilibrated with 0.05 M ammonium bicarbonate buffer at pH 8.0 and subsequently eluted with an ammonium bicarbonate concentration gradient from 0.05 to 0.5 M at constant pH (8.0) and temperature (25 degrees C). The fraction which eluted last (M-VI) showed, after direct lyophilization, a single band by polyacrylamide gel electrophoresis (PAGE) and SDS-PAGE, indicating an approximate M,. of 14 000 and 77 000, in the presence and absence of dithiothreitol, respectively. Its amino acid composition revealed a high level of hydrophobic and basic amino acids as well as 13 half-cystine residues. Its isoelectric point and extinction coefficient (E-1.0cm(1.0mg/ml) at 278 nm and pH 7.0) were 8.2 and 1.170, respectively. M-VI was devoid of phospholipase A(2) (PLA(2)) activity on egg yolk, as well as of hemorrhagic, anticoagulant and coagulant activities, but could induce drastic necrosis on skeletal muscle fibres as well as rapid and transient edema on the rat paw. Its N-terminal sequence: SLFELGKMILQETGKNPAKSYGVYGCNCGVGGRGKPKDATDRCCYVHKCCYK.... revealed high homology with other Lys 49 PLA(2)-like myotoxins from other bothropic venoms. Orthorhombic crystals of M-VI? which diffracted to a maximal resolution of 1.6 Angstrom. were obtained and indicated the presence of a dimer in the asymmetrical unit. (C) 1998 Elsevier B.V. Ltd. All rights reserved.